To What Extent Do the Investment Programs in the Small and Medium Enterprises Sector Comply with the Determinants of National Competitive Advantage? - Islam, K. M. Anwarul; Barghouthi, Orobah Ali (International Journal of Small and Medium Enterprises, 2018)
The analysis of the researcher was corroborated by the expert opinion.In the interview researcher said that, the base is small and medium enterprises, the Palestinian economy is dominated by small and medium family-owned businesses: more than 85% of all establishments are owned by a single individual. Private and public shareholder companies and partnerships constitute less than 11% of all firms. The first and most important step is to establish governance in SMS & Establishing partnerships in shape of fund of funds, we have 6 funds, 60 million fund for industry, fund for agriculture, fund for microfinance, fund for Gazza, Jerusalem, fund convertible process, is not money wise but convincing the owners to change the way of working is the most impediment.According to Porter, competitive advantage results from the presence of world- class institutions that first create specialized factors and then continually work to upgrade them. Additional steps to be undertaken according to Mustafa, SMEs widen and open new markets and further invest in local markets and sponsor high-tech industries. The analysis of the researcher was corroborated by the expert opinion.In the interview researcher said that, the base is small and medium enterprises, the Palestinian economy is dominated by small and medium family-owned businesses: more than 85% of all establishments are owned by a single individual. Private and public shareholder companies and partnerships constitute less than 11% of all firms. The first and most important step is to establish governance in SMS & Establishing partnerships in shape of fund of funds, we have 6 funds, 60 million fund for industry, fund for agriculture, fund for microfinance, fund for Gazza, Jerusalem, fund convertible process, is not money wise but convincing the owners to change the way of working is the most impediment.According to Porter, competitive advantage results from the presence of world- class institutions that first create specialized factors and then continually work to upgrade them. Additional steps to be undertaken according to Mustafa, SMEs widen and open new markets and further invest in local markets and sponsor high-tech industries.